Toilet training: what can the cookstove sector learn from improved sanitation promotion?. Issue 6 (2nd November 2018) - Sesan, Temilade; Jewitt, Sarah; Clifford, Mike; Ray, Charlotte
ABSTRACT: Within the domain of public health, commonalities exist between the sanitation and cookstove sectors. Despite these commonalities and the grounds established for cross-learning between both sectors, however, there has not been much evidence of knowledge exchange across them to date. Our paper frames this as a missed opportunity for the cookstove sector, given the capacity for user-centred innovation and multi-scale approaches demonstrated in the sanitation sector. The paper highlights points of convergence and divergence in the approaches used in both sectors, with particular focus on behaviour change approaches that go beyond the level of the individual. The analysis highlights the importance of the enabling environment, community-focused approaches and locally specific contextual factors in promoting behavioural change in the sanitation sector. Our paper makes a case for the application of such approaches to cookstove interventions, especially in light of their ability to drive sustained change by matching demand-side motivations with supply-side opportunities. Abbreviation : DALY: Disability-adjusted life year; CHC: Community Health Club; CLTS: Community-Led Total Sanitation; HAP: Household air pollution; BM-WASH: Integrated Behavioural Model for Water, Sanitation and Hygiene; ICS: Improved cookstove; LPG: Liquefied petroleum gas; NBA: Nirmal Bharat Abhiyan; NGO: Non:governmental organisation; OD: Open defecation; ODF: Open defecation free; HAST: Participatory Hygiene and Sanitation Transformation; RANAS: Risks, Attitudes, Norms, Abilities and Self–regulation RCT: Randomised controlled trial; (Sani) FOAM: Focus, Opportunity, Ability and Motivation; SBM: Swachh Bharat Mission; TSC: Total Sanitation Campaign; WASH: Water, Sanitation and Hygiene